Aktywność innowacyjna a wzrost gospodarczy - Misiak, Tomasz (The Innovative Activity Against the Economic Growth, 2006)
The aim of this article is to theoretically present the innovations influence on the economic growth. It also includes the presentation of selected indexes of Polish innovative activity against the background of some countries. The conducted financial analyses concern such countries as: USA, Japan, Finland, Sweden, Germany. It will make possible to define some basic differences and similarities. In the paper there was intentionally chosen the economy of the richest countries. These countries are strongly encouraging the innovations which are the main factors that determine the economic growth. It is allowed to say that comparison between Poland and leaders of innovations is quite reasonable. The substantiation for this is the benchmarking practice and according to that the behavior patterns should be obtained from the best ones.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 539-546